Feeling at home: Sound, affect and domesticity on radio soap operas. (1st April 2021) - Emmett, Ilana R.
This article introduces the concept of 'the everyday implausible', asserting that, between 1930 and 1960, US radio serial aesthetics produced a tug-of-war between the familiar and the unfamiliar that was simultaneously radical and reactionary. This aesthetic created a space for the listener to place new versions of herself within the narrative, inviting the imagined woman-at-home to re-envisioning the possibilities of reality. However, re-envisioning reality produced its own set of limitations. The sonic features of the radio serial soundscape created imaginary spaces within the home, but these imaginary spaces were ‐ as often as not ‐ also homes, making the potential of escape wholly illusory. In giving attention to the specific aesthetic features of these programmes, this article interrogates the meaningful work produced by a sparse soundscape, alongside an emphasis on domesticity and emotional conversation.